Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Corn - Alan J. Schlegel; H. Dewayne Bond (Kansas Agricultural Experiment Station Research Reports, 2020)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated corn in western Kansas. In 2019, N applied alone increased yields by 71 bu/a, whereas P applied alone increased yields by 10 bu/a. Nitrogen and P applied together increased yields up to 131 bu/a, which is 10 bu/a less than the 10-year average of 141 bu/a. Application of 120 lb/a N (with highest P rate) produced 97% of maximum yield in 2019, which is slightly greater than the 10-year average. Application of 80 instead of 40 lb P2O5/a increased average yields by 4 bu/a. Average grain N content reached a maximum of 0.6 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu). At the highest N and P rate, apparent fertilizer nitrogen recovery in the grain (AFNRg) was 41% and apparent fertilizer phosphorus recovery in the grain (AFPRg) was 60%.
Keywords: nitrogen fertilization; phosphorus fertilization; irrigated corn; long-term fertility; nutrient removal